A cause for academic euphoria: Seven BTS songs that inspire the learning and teaching of services marketing (Journal of Applied Learning and Teaching, 2025)
Songs have been used as an effective learning tool in marketing. Despite the popularity of the K-pop group BTS in popular culture and the importance of services marketing in academia and industry, few studies have examined BTS through the lens of learning services marketing. This opinion piece discusses the services marketing lessons that can be inspired by the songs of BTS. A BTS-Services Marketing Playlist compiling seven selected BTS songs is introduced that captures and synthesizes key fundamental as well as contemporary themes in the services marketing literature. The integrated list of topics and consolidated key literature in the playlist can inspire future research directions for researchers who aim to specialize in the services marketing field. Further, the playlist is a useful compilation that can guide content creation and lesson planning for higher education programs in services marketing. This paper is one of the first to connect K-pop songs to services marketing and pedagogy and contributes to the literature on using the arts for the teaching and advancement of services marketing education.